Generalized mechanics of flexure hinges for unified simulations. (October 2019) - Xu, Siqiang; Liu, Pinkuan
Abstract: Flexure hinges are widely introduced into precision mechanisms to perform the smooth motion without backlash and friction. In this paper, a generalized beam element based on the weak form quadrature element method is proposed to assess the compliances of the flexure hinges with different profiles. The flexure hinge is regarded as the Timoshenko beam taking the shearing effect into account. The elemental stiffness matrix is obtained with solution of algebraic equations and the explicit mesh structure is not required for compliance modelling of the flexure hinge with an arbitrary profile. The compliances of two typical types of flexure hinges are computed based on the proposed element. The results are compared with ones yielded by analytical equations. Then the high accuracy and effectiveness of the proposed element are validated.